Comparison of conventional and molecular techniques for Trypanosoma vivax diagnosis in experimentally infected cattle - Fidelis Junior, Otavio Luiz [UNESP]; Sampaio, Paulo Henrique [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP]; Wijffels, Gene; Cadioli, Fabiano Antonio [UNESP] (FapUNIFESP (SciELO), 2019)
Livestock infections by Trypanosoma vivax have been occurring with increasing frequency, mainly due to the presence of animals with subclinical infections and without apparent parasitaemia, making diagnosis challenging. The aim of the present study was to evaluate several techniques used for T. vivax diagnosis in order to assess the best way of using them during the course of the disease. Molecular methods demonstrated higher rates of detection than parasitological methods, detecting 33 of the 54 (61.1%) known positive samples, while the hematocrit centrifugation technique (best parasitological test) detected only 44.4%. The serological methods, IFAT and ELISA, detected seropositivity in 51 of the 54 (94.4%) and 49 of the 54 (90.7%) known positive samples, respectively. Despite being highly sensitive, the latter only demonstrates exposure to the infectious agent and does not indicate whether the infection is active. The present study was the first to use the qPCR for a South American isolate, improving disease detection and quantification. Furthermore, the analyses revealed that the patent phase of the disease may extend up to 42 days, longer than previously reported. The combination of several diagnostic techniques can lower the frequency of false negative results and contributes toward better disease control.
Comparação de técnicas convencionais e moleculares para diagnóstico em bovinos experimentalmente infectados por Trypanosoma vivax
Keywords: Diagnosis; PCR; QPCR; Serology; Trypanosomosis